2013
DOI: 10.1136/ejhpharm-2012-000263
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacist–patient counselling in Dubai: assessment and reflection on patient satisfaction

Abstract: Objectives The aim of the present study was to evaluate the counselling services provided by outpatient pharmacists using the criteria specified by Medication Counseling Behaviour Guideline (US Pharmacopoeia (USP) 1997). The study also assessed the perceptions of patients and pharmacists with regard to counselling. Methods The study was carried out over a period of 5 months at outpatient pharmacies located in different regions of Dubai. The study design included structured observation of over 700 pharmacist–p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
11
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 15 publications
6
11
1
Order By: Relevance
“…Our study findings are consistent with those of the previous study conducted in Dubai. 11 We found similar patients satisfaction level with the pharmacist counseling practice. However, in Dubai study, men, older patients, and patient with low educational level reported higher level of satisfaction compared to others categories.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Our study findings are consistent with those of the previous study conducted in Dubai. 11 We found similar patients satisfaction level with the pharmacist counseling practice. However, in Dubai study, men, older patients, and patient with low educational level reported higher level of satisfaction compared to others categories.…”
Section: Discussionsupporting
confidence: 69%
“…When compared to other study that was conducted in community pharmacy in Riyadh in 2012, 11 findings of our survey show better patient counseling by pharmacist from patient prospective. Our participants also were more appreciated to the patient education sessions carried by pharmacist regarding the medications-related problems (80% vs. 43%).…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Another study conducted in Dubai, United Arab Emirates 11 , aimed to evaluate the outpatient pharmacists counseling practice and to assess the patients' perceptions of their pharmacist using USP-MCB guidelines. The authors reported that almost 42% of the study participants did not receive counseling from their pharmacists although the patients were believed that they need it.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16][17] It is important for pharmacy professionals to possess effective consultation skills as they can help improve medication adherence and also improve patient satisfaction, leading to better outcomes. 9,18,19 Therefore, there is a need for improving pharmacy professionals' consultation skills to enable them to support patients effectively. 20,21 In the UK, there is increasing demand for pharmacy professionals to possess effective consultation skills due to changes in the services pharmacies are expected provide in their contract with the National Health Service (NHS).…”
Section: Introductionmentioning
confidence: 99%